Comparing the performance of different geometric solutions for erosion problem of standard elbows in air-solid flow using CFD-DEM. (19th June 2023) - Beyralvand, Davood; Banazadeh, Farzad; Moghaddas, Rasoul
In many industrial applications, sand erosion wear is the main cause of equipment failure, particularly in the transferring pipeline fittings. In order to reduce the adverse consequences of erosion in bends, this work investigates the erosion of an elbow pipe due to the gas-solids turbulent pipe flow using computational fluid dynamics (CFD). The studied geometries included double T-plug, elbows with different curvature radius, elbows with different angles, T-plug and vortex chamber elbow. Results of the sensitivity analyses used to study the effects of the changes in the particle size/velocity, mass loading, erosion model and turbulence model on erosion rate revealed that long-radius elbow and double T-plug are good choices.